2013
DOI: 10.1088/0952-4746/33/2/r17
|View full text |Cite
|
Sign up to set email alerts
|

A review of the behaviour of U-238 series radionuclides in soils and plants

Abstract: The U-238 series of radionuclides is of relevance in a variety of environmental contexts ranging from the remediation of former uranium mining and milling facilities to the deep geological disposal of solid radioactive wastes. Herein, we review what is known concerning the behaviour of radionuclides from the U-238 decay chain in soils and plants. This review is intended to provide a single comprehensive source of information to anyone involved in undertaking environmental impact assessment studies relating to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 82 publications
0
46
0
5
Order By: Relevance
“…In their recent study, Wang et al [191] found that volatile organic compounds released by plant growth-promoting rhizobacteria increases both selenium and iron uptake. Uranium is another geogenic, potentially toxic contaminant [192] and studies in nutrient culture show its uptake by crops [193,194]. Several studies confirmed that irrigation water contaminated with uranium has an impact on crop quality though less to soil contamination by uranium [195][196][197].…”
Section: Geogenic Contaminants In Irrigation Watermentioning
confidence: 99%
“…In their recent study, Wang et al [191] found that volatile organic compounds released by plant growth-promoting rhizobacteria increases both selenium and iron uptake. Uranium is another geogenic, potentially toxic contaminant [192] and studies in nutrient culture show its uptake by crops [193,194]. Several studies confirmed that irrigation water contaminated with uranium has an impact on crop quality though less to soil contamination by uranium [195][196][197].…”
Section: Geogenic Contaminants In Irrigation Watermentioning
confidence: 99%
“…However, there is only a limited literature on such upward transport. Furthermore, information on the sorption of these radionuclides to soils and their availability for plant uptake has recently been reviewed (Mitchell et al, 2013), providing an updated source of information relevant to modelling the transport and uptake of U-series radionuclides. Also in a previous paper (Pérez-Sánchez and Thorne, 2014); a mathematical model for the behaviour of 238 U-series in soils and plants was described for dose assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Na argila, esses radionuclídeos podem adsorver por troca iônica em sua superfície, ou por formação de complexos firmemente aderidos. Já os compostos orgânicos atuam como coletores naturais de elementos radioativos; mas também podem formar complexos orgânicos ou coloides, aumentando a sua mobilidade (Rachkova et al, 2010;Mitchell et al, 2013;Peixoto, 2013). Embora os teores de matéria orgânica nos solos amostrados sejam aproximados (13 e 10 g dm -3 para os solos arenoso e argiloso respectivamente), o teor de argila do solo argiloso é quase quatro vezes maior que do solo arenoso, e contribui para a maior concentração dos radionuclídeos.…”
Section: Precisão E Exatidão Das Metodologias Utilizadasunclassified
“…Além disso, a adsorção de radionuclídeos em solos ácidos está diretamente relacionada com sua capacidade de troca catiônica (Rachkova et al, 2010) águas naturais é muito baixa, sendo que até 90% desta concentração está associada com a fase coloidal em suspensão, e tem relação direta com a presença de substâncias orgânicas no solo (Rachkova et al, 2010;Mitchell et al, 2013). Ao contrário do tório, o urânio possui duas formas iônicas principais: além da +4 uma outra +6.…”
Section: Precisão E Exatidão Das Metodologias Utilizadasunclassified
See 1 more Smart Citation